2014 International Conference on Engineering, Technology and Innovation (ICE) 2014
DOI: 10.1109/ice.2014.6871574
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of technological innovation capabilities and business innovation capabilities on organization performance: Preliminary findings of Malaysian food processing SMEs

Abstract: Abstract-Due to the increasing of global competitive pressure, shortened product life cycles and ease of imitation, organizations must continue to innovate to ensure the organization sustainability. One of the major factors contributing to organization sustainability is innovation. Previous studies have shown significant impact of organizational innovation capabilities on product and service quality. Literature has identified various types of innovation in organization. Among them are business innovation capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…These factors were influenced by business innovation capabilities, including ad-ministrative innovation, management practices, and organizational structure, as well as technological innovations that affected learning capabilities, resource allocation capabilities, and manufacturing capabilities. Another study reported that innovation capabilities have a significant impact on the performance of a firm, and innovation capabilities are an essential factor that predicts the performance of firms (Aziati et al 2014).…”
Section: Technological Innovation To Innovative Performance and Attit...mentioning
confidence: 99%
“…These factors were influenced by business innovation capabilities, including ad-ministrative innovation, management practices, and organizational structure, as well as technological innovations that affected learning capabilities, resource allocation capabilities, and manufacturing capabilities. Another study reported that innovation capabilities have a significant impact on the performance of a firm, and innovation capabilities are an essential factor that predicts the performance of firms (Aziati et al 2014).…”
Section: Technological Innovation To Innovative Performance and Attit...mentioning
confidence: 99%
“…Innovation appears in these approaches as an important vector for sustainability (Schaltegger et al, 2016). In other words, one of the main factors that contribute to the sustainability of a firm is its capability for innovation (Aziati et al, 2014).…”
Section: Innovation Capability and Sustainabilitymentioning
confidence: 99%
“…In recent decades, different views of sustainability (economic, social and environmental) and innovation capability have started to be relevant issues in several studies around the world (Chang et al, 2017;Kong et al, 2016;Su et al, 2017;Serrano-Garc ıa et al, 2021). The union of these themes emerged as a field of research for firms that want to remain competitive and sustainable in an environment of rapid change (Aziati et al, 2014), which takes place in a scenario of climate change and global biodiversity loss (Ostermann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The organizational performance refers to how organizational operations perform. It is considered as the most important measure of success in commercial sector [37].Previous studies have shown significant impact of organizational innovation capabilities on the performance [11]. A firm's survival is based on its performance [64].…”
Section: Introductionmentioning
confidence: 99%
“…According to the resource-based view, technological innovation capability can secure the firm with a competitive advantage [17]. Firms must continue to innovate to ensure the thier sustainability in the environment of global competitive pressure, and due to shortened product life cycles [11]. SMEs need to become more competitive and sustainable by boosting their technological innovation capabilities to survive and grow in an era of uncertainty [64].…”
Section: Introductionmentioning
confidence: 99%